Effect of static annealing on superplastic behavior of a friction stir welded Ti-6Al-4V alloy joint and microstructural evolution during deformation. (10th December 2022) - Jia, C.L.; Wu, L.H.; Xue, P.; Ni, D.R.; Xiao, B.L.; Ma, Z.Y.
Highlights: A new process of FSW + static annealing + superplastic deformation was proposed to eliminate strain localization. Similar superplastic abilities were obtained in the BM and NZ with totally different structures. An optimized view on the classical Langdon theory was put forward in the field of superplasticity. The mechanisms of the spheroidization of lamellae and the fragmentation of equiaxed grains were discussed. This study provides a new way to fabricate large-scale complex Ti alloy components. Abstract: Structural integration is one of the most critical developing directions in the modern aerospace field, in which large-scale complex components of Ti alloys are proposed to be fabricated via the method of welding + superplastic forming. However, the undesired strain localization appeared during superplastic deformation of the entire joint has largely hindered the development of this method. In our study, a combination process of friction stir welding (FSW) + static annealing + superplastic deformation was first time proposed to eliminate severe local deformation. To achieve this result, a fully fine lamellar structure was obtained in the nugget zone (NZ) via FSW, which was totally different from the mill-annealed structure in the base material (BM). After annealing at 900 °C for 180 min, the BM and NZ then exhibited the similar elongation of > 500% and similar flow stress at 900 °C, 3 × 10 −3 s −1, which was the precondition for achieving uniform superplastic deformation in the entire joint. Moreover, the different microstructures in the BM and NZ tended to become the similar equiaxed structure after deformation, which was the result of different microstructural evolution mechanisms in the NZ and BM. For the NZ, there was a static and dynamic spheroidization of the fully lamellar structure during the process, which could largely reduce the flow softening of the fully lamellar structure. For the BM, a new view of "Langdon-CRSS theory" (CRSS, critical resolved shear stress) was proposed to describe the fragmentation of the coarse equiaxed structure, which established the relationship between grain boundary sliding and intragranular deformation during deformation.